The relevance of Sa'id Nursi's approach in dealing with New Atheism : an analysis - Muhammad Faris Fahmi Mohd Isa (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research studies the ideology and argument proposed by the New Atheism, a group of outspoken atheists that emerges during the early course of the twenty-first century. Unlike the “old” atheism that particularly engages in philosophical-based reasoning, this new wave of atheistic movement on the other hand is built upon scientific-grounded arguments with their aim to publicly expose and criticise the tenets and practices of religions, especially of Islam. Among the New Atheists many ideas, the researcher highlights three major arguments laid by them, specifically by their Four Horseman, which are issues circulating the idea of God, religion and morality. These points are then analysed and evaluated in the light of Bediuzzaman Sa'id Nursi views that are extracted from his magnum opus, the Risale-i Nur with a specific reference to its first volume, The Words. Though Risale-i Nur is commonly deemed as a spiritual-laden treatise, in contrast with the more scientific-driven New Atheism, the researcher argues that this work of Sa'īd Nursī is nonetheless relevant and corresponding to the arguments brought about by the latter, especially in the discussion of God existence using the teleological arguments or the argument from design. The researcher concludes that Sa'īd Nursī's arguments remain applicable to the disputes raised by the New Atheism, albeit the fact that his work has been written years before the emergence of the latter, thus demonstrating its credential to be mainly referred in this research.